انسانی جان کی حرمت اور قتلِ ناحق پر سزا و سرزنش: ایک قرآنی، فقہی و آئینی مطالعہ: The Sanctity of Human Life and the Divine Retribution for Unlawful Killing: A Qur’anic, Jurisprudential, and Constitutional Study (Al-NASR, 2023)
This research paper explores the sanctity of human life and the divine condemnation of unlawful killing in Islam, examined through Qur’anic injunctions, Prophetic traditions, and classical as well as modern juristic interpretations. The study further contextualizes these principles within the framework of the Constitution of Pakistan and the contemporary phenomenon of state violence, especially the unjustified killings of peaceful protestors by law enforcement agencies. The Qur’an presents the preservation of human life as one of the foremost objectives of Shari‘ah (Maqāṣid al-Sharī‘ah), equating the killing of a single innocent soul to the murder of all humanity (al-Mā’idah: 32). Prophetic teachings emphasize that shedding innocent blood is among the gravest sins, leading to divine wrath and eternal punishment. Classical jurists such as Imām Māwardī, Ibn Qudāmah, and al-Sarakhsī affirm that no authority — including the state — possesses the right to take life without just cause and due judicial process.The paper also examines the constitutional provisions of Pakistan, notably Articles 9 and 14, which safeguard life and human dignity. Despite these guarantees, repeated incidents of extrajudicial killings and state oppression highlight a moral and legal failure that contradicts both Islamic and constitutional norms. The research concludes that the sanctity of human life is an inviolable trust (amānah) granted by God, and any violation — whether by individuals or state institutions — constitutes an act of fasād fī al-arḍ (corruption on earth). It calls for comprehensive legal and ethical reforms, the enforcement of qiṣāṣ and accountability without discrimination, and the re-establishment of a justice system rooted in Qur’anic principles of mercy, equality, and human dignity.
Keywords: Sanctity of Life; Unlawful Killing; Islamic Jurisprudence; Human Rights in Islam; Constitutional Justice; Qur’anic and Prophetic Ethics; Qur’anic Studies; Hadith Studies; Islamic Ethics